Taxonomic novelties of Greigia (Bromelioideae, Bromeliaceae) for the Northern Andes - Llanos-Prieto, Alejandro; Betancur, Julio; Aguirre-Santoro, Julián (Phytotaxa, 2025)
The genus Greigia (Bromeliaceae: Bromelioideae) is distributed from the Valdivian temperate forest in Chile to southern Mexico, with the highest species richness found in the high-elevation and humid areas of the tropical Andes. As part of a forthcoming taxonomic revision of Greigia, we have identified several taxonomic and chorological novelties in Colombia and Ecuador, which we present here. First, we describe seven new species: G. antioquiensis, G. chingazaensis, G. collinoides, G. longicaulis, G. muysca, G. sumapazensis and G. transandina. Second, we propose a change of status for G. mulfordii var. macrantha. Finally, we report the occurrence of G. tillettii in Colombia, a species previously known only from its type collection in Venezuela. For the new taxa, we provide diagnosis, morphological descriptions, illustrations, photographs, and comments on their taxonomic affinities and distribution. We also provide proposals of extinction risks assessments for all the taxa using the IUCN guidelines.